IMF Staff Papers, Volume 53, No. 1. (IMF Staff Papers; IMF Staff Papers ;, 2006)
This first issue for 2006 is anchored by two papers on Russia. The opening paper discusses Russia and the World Trade Organization, and the concluding paper, by John Odling-Smee (former Director of the IMF's European II Department), presents a comprehensive and authoritative history of the IMF's relations with Russia during the 1990s. Other articles in this issue cover rent-seeking behavior, estimations of government net capital stocks, and three papers cover different aspects of exchange rates.